2014
DOI: 10.1097/cad.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Abiraterone in heavily pretreated patients with metastatic castrate-resistant prostate cancer

Abstract: The aim of this study was to evaluate the activity and tolerability of abiraterone acetate in patients with metastatic castrate-resistant prostate cancer treated previously with more than three lines of chemotherapy. Patients received 1 g of abiraterone acetate (administered as four 250 mg tablets) orally once daily with prednisone at a dose of 5 mg orally twice daily. The primary endpoint was prostate-specific antigen (PSA) response. From August 2011 to January 2013, 36 patients were enrolled. PSA response wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Five of the 15 patients received Enz immediately after AA; however, no response rates were presented for these 5 patients. Another study reported on 36 patients treated with AA as a fourth-line or fifth-line treatment [23,25]. The OS in this group was 68 weeks; however, these patients were not pretreated with Enz or AA, but were treated with three lines of chemotherapy (Doc and Cab).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the 15 patients received Enz immediately after AA; however, no response rates were presented for these 5 patients. Another study reported on 36 patients treated with AA as a fourth-line or fifth-line treatment [23,25]. The OS in this group was 68 weeks; however, these patients were not pretreated with Enz or AA, but were treated with three lines of chemotherapy (Doc and Cab).…”
Section: Discussionmentioning
confidence: 99%
“…The number of reports on fourth-line therapies in mCRPC patients is limited, based on small cohorts and all are retrospective [18,23,24,25]. One study reports on 38 patients treated with miscellaneous fourth-line treatments, with an OS of 20 weeks [18].…”
Section: Discussionmentioning
confidence: 99%